Microscopic Colitis and Colorectal Neoplastic Lesion Rate in Chronic Nonbloody Diarrhea: A Prospective, Multicenter Study. Issue 5 (27th March 2014) - Tontini, Gian Eugenio; Pastorelli, Luca; Spina, Luisa; Fabris, Federica; Bruni, Barbara; Clemente, Claudio; de Nucci, Germana; Cavallaro, Flaminia; Marconi, Stefano; Neurath, Markus F.; Neumann, Helmut; Tacconi, Milena; et al.
Abstract : Background: Lymphocytic and collagenous colitis are emerging as common findings in subjects undergoing colonoscopy for chronic non-bloody diarrhea (CNBD). Data concerning microscopic colitis (MC) are still limited and affected by controversial epidemiological evidences. Recent converging lines of evidence suggest that MC correlates a lower risk of colorectal neoplasia. Accordingly, we prospectively assessed MC prevalence in a multicenter cohort of subjects submitted to colonoscopy for CNBD, thereby defining whether MC influences the risk of colorectal neoplasia. Methods: Consecutive patients with CNBD of unknown origin underwent pan-colonoscopy with multiple biopsies. The prevalence of neoplastic patients in MC was compared with that observed in negative CNBD subjects. Results: Among 8006 colonoscopy, 305 subjects were enrolled for CNBD. Patients with CNBD were more likely to be women than men (odds ratio = 1.5; P = 0.001). Histopathology detected high prevalence of MC (16%) with a clear predominance of collagenous colitis (70%). A striking age-dependent rise in MC-associated risk was observed, depicting outstanding differences among varying age groups, as in the number needed to screen 1 new case. Gender distribution was balanced within MC patients (Female/Male = 1.5/1), especially among lymphocytic colitis (Female/Male = 1.2/1). MC patients were negatively associated with the risk of neoplastic polyps compared with negative CNBD subjects (odds ratio = 0.22; P = 0.035). Conclusions: MC is the first cause of CNBD in subjects submitted to colonoscopy. Multiple biopsies are strongly recommended, even in the case of uneventful endoscopic inspection, especially for age ≥40 years. MC has a reduced risk of colorectal neoplasia, suggesting that this model of chronic inflammation plays a protective effect against colorectal carcinogenesis.